Resin composition, pellet and molded body
Patent Information
- Application Number
- JP2024150035
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-06-19
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-14
AI Technical Summary
【0015】 本発明によれば、使用時には樹脂製のバッテリーケースと金属板(冷却プレート)との接着性が良好であり、かつ解体時には、筐体から上記金属板を容易に剥離することができる接着性の樹脂組成物、又は、常時は熱伝導性が良好であり、かつ熱暴走時には断熱性に優れる相反する性質を備える接着性の樹脂組成物を提供することができる。
Smart Images

Figure 2025036375000002 
Figure 2025036375000003 
Figure 2025036375000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition, pellets containing the resin composition, and a molded article obtained by molding the resin composition. [Background technology]
[0002] Thermoplastic resin compositions with excellent moldability are also excellent in recyclability and light weight, and thus their molded articles are used in various applications such as machinery, electrical and electronic equipment, office automation equipment, automotive interior and exterior materials, electric vehicles, etc. In particular, they are expected to be used in electric vehicles and hybrid vehicles, as described below.
[0003] As part of environmental measures, research and development of electric vehicles and hybrid vehicles is progressing, and the development of high-energy density batteries and lightweight vehicles is being actively pursued with the aim of improving driving range.
[0004] Battery packs used in electric vehicles and hybrid vehicles have a structure in which a large number of battery modules, each including a number of battery cells, are connected together to obtain high output. Each battery cell includes positive and negative electrode current collectors, separators, active materials, electrolytes, etc., and can be repeatedly charged and discharged through electrochemical reactions between these elements. In recent years, there has been an increasing need for batteries with large capacity, including for use as an energy storage source, and there is a demand for battery packs with a multi-module structure comprising a large number of battery modules in which a large number of secondary batteries are connected in series or in parallel.
[0005] In a multi-module battery pack, many secondary batteries are densely packed in a small space, so it is important to easily release the heat generated from each secondary battery. During the charging / discharging process of a secondary battery, heat is generated by electrochemical reactions. If the heat generated in the battery module during the charging / discharging process is not effectively removed, heat accumulation occurs, accelerating the deterioration of the battery module and in some cases, it may lead to fire or explosion. Therefore, in order to cool the secondary batteries, a cooling plate having a cooling passage that is laid on the bottom of the battery pack is provided in a high-output, large-capacity battery module and a battery pack equipped with the battery module. A metal plate made of aluminum or the like may be installed as the cooling plate (see, for example, Patent Document 1).
[0006] Conventionally, battery casings have been made of metal, but resin casings are beginning to be used to reduce the weight of batteries and improve their recyclability. When using a resin casing, an adhesive sheet for bonding the metal plate for releasing heat to the resin casing is important.
[0007] A high-output, large-capacity battery module and a battery pack equipped with the battery module require a cooling device for cooling the battery cells contained therein. Since the power that can be produced by one battery cell is not large, a required number of battery cells are generally stacked and packaged in a module case. In order to cool the heat generated in the electricity production process in each battery cell and to maintain the temperature of the secondary battery at an appropriate level, a plurality of cooling fins corresponding to the area of the battery cells are inserted between the battery cells as heat dissipation members. The plurality of cooling fins that absorb heat from each battery cell are connected to one cooling plate and transfer the heat to the cooling plate. The cooling plate transfers the heat transferred from the cooling fins to a heat sink, and the heat sink is cooled by cooling water or cooling air.
[0008] In general, when a battery cell and a cooling fin are combined, a heat transfer material capable of minimizing thermal resistance between the contact interfaces is applied to the interfaces to bond the battery cell and the cooling fin. However, since it is difficult to uniformly apply the heat transfer material to the areas of the battery cell and the cooling fin, the cooling performance may decrease due to unevenness of the contact surface after drying. In addition, if the battery cell swells, the cooling performance may decrease due to separation of the contact surface, and the contact interface may separate when the battery cell is used for a long period of time. In response to the above problems, Patent Document 1 proposes a battery module that includes a plurality of battery cells arranged facing each other and aligned in at least one direction, a cooling plate located below the plurality of battery cells, and a heat transfer tape that transfers heat from the battery cells to the cooling plate and is adhered to the battery cells. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Special Publication No. 2018-530896 Summary of the Invention [Problem to be solved by the invention]
[0010] As described above, when the housing is made of resin, a metal plate for releasing heat and an adhesive sheet for bonding the metal plate to the resin housing are important, and since the adhesive sheet is required to bond different materials, a material with high adhesive strength and high thermal conductivity is required. On the other hand, when considering the recycling of batteries, it is necessary to dismantle old batteries, but as described above, if the adhesive strength of the adhesive sheet is increased, there is a problem that dismantling is difficult.
[0011] The battery module disclosed in Patent Document 1 is preferable because it effectively transfers heat from the battery cells to the cooling plate under normal conditions, but when one battery cell experiences thermal runaway, the heat from the battery cell is transferred to other nearby battery cells via the cooling plate, causing a chain reaction of thermal runaway. For this reason, it is preferable for the battery module to have thermal insulation that thermally isolates the battery cells from the cooling plate during thermal runaway.
[0012] Therefore, an object of the present invention is to provide an adhesive resin composition that has good adhesion between a resin battery case and a metal plate (cooling plate) during use and that allows the metal plate to be easily peeled off from the casing during disassembly, or an adhesive resin composition that has the contradictory properties of good thermal conductivity at all times and excellent insulating properties during thermal runaway. [Means for solving the problem]
[0013] As a result of extensive investigations, the present inventors have found that a resin composition having a specific formulation can solve the above problems, and have thus completed the present invention. That is, the present invention provides the following.
[0014] [1] A resin composition comprising a modified polyolefin resin (A), a thermally expandable flame retardant (Ba), and a copolymer of an α-olefin and an unsaturated carboxylic acid (C). [2] The resin composition according to the above [1], wherein the thermally expandable flame retardant (Ba) comprises a compound having a melamine structure or a piperazine structure. [3] The resin composition according to the above [1] or [2], wherein the thermally expandable flame retardant (Ba) includes an intumescent flame retardant. [4] A resin composition comprising a modified polyolefin resin (A), a thermally expandable foaming agent (Bb), and a copolymer of an α-olefin and an unsaturated carboxylic acid (C). [5] The resin composition according to the above [4], wherein the thermally expandable foaming agent (Bb) comprises a chemical foaming agent and / or a physical foaming agent, and a thermoplastic resin capsule encapsulating the chemical foaming agent and / or the physical foaming agent. [6] The resin composition according to the above [4] or [5], wherein the thermally expandable foaming agent (Bb) comprises a physical foaming agent containing a hydrocarbon compound and a thermoplastic resin capsule encapsulating the physical foaming agent and the thermoplastic resin capsule. [7] The resin composition according to any one of the above [1] to [6], wherein the unsaturated carboxylic acid in the copolymer (C) of an α-olefin and an unsaturated carboxylic acid includes maleic anhydride. [8] The resin composition according to any one of the above [1] to [3] or the above [7], wherein the proportion of the thermally expandable flame retardant (Ba) relative to the total mass of the resin composition is 35 mass% or more. [9] The resin composition according to any one of the above [4] to [7], wherein the proportion of the thermally expandable foaming agent (Bb) relative to the total mass of the resin composition is 1 mass % or more.
[10] The resin composition according to any one of the above [1] to [9], wherein the modified polyolefin resin (A) is graft-modified with an unsaturated carboxylic acid and / or a derivative thereof.
[11] The resin composition according to any one of the above [1] to
[10] , wherein the modified polyolefin resin (A) has a melting point of 150° C. or lower.
[12] The resin composition according to any one of the above [1] to
[11] , further comprising a polyethylene resin (D).
[13] The resin composition according to any one of the above [1] to
[12] , further comprising a polypropylene-based resin (E).
[14] A pellet comprising the resin composition according to any one of the above [1] to
[13] .
[15] A molded article obtained by molding the resin composition according to any one of the above [1] to
[13] . Effect of the Invention
[0015] According to the present invention, it is possible to provide an adhesive resin composition that has good adhesion between a resin battery case and a metal plate (cooling plate) during use and that allows the metal plate to be easily peeled off from the housing when dismantled, or an adhesive resin composition that has the contradictory properties of good thermal conductivity at all times and excellent insulating properties during thermal runaway. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a conceptual diagram showing a battery pack in which the resin composition of the present invention can be used. [Diagram 2] FIG. 2 is another conceptual diagram showing a battery pack in which the resin composition of the present invention can be used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention (hereinafter, sometimes referred to as the present embodiment) will be described in detail. However, the following description is merely an example of the embodiment, and the present invention is not limited to this in any way.
[0018] [Resin composition] The resin composition according to the present invention (hereinafter, sometimes referred to as the present resin composition) contains a modified polyolefin resin (A), a thermally expandable flame retardant (Ba) or a thermally expandable foaming agent (Bb), and a copolymer (C) of an α-olefin and an unsaturated carboxylic acid. By having this composition, for example, seemingly contradictory properties such as high adhesion between different materials when the battery is used and easy dismantling when recycling, or good thermal conductivity when the battery is used and heat insulation during thermal runaway can be achieved at the same time. The resin composition contains a thermally expandable flame retardant (Ba) and a thermally expandable foaming agent (Bb) as a thermally expandable material (B), and when heated, the molded article obtained by molding the resin composition expands, reducing the adhesion between the resin casing and the metal plate and making it easier to peel them off. In addition, since the resin composition contains a thermally expandable flame retardant (Ba) and a thermally expandable foaming agent (Bb) as the thermally expandable material (B), when the battery cell is in an abnormally high temperature state, the molded body obtained by molding the resin composition heats and expands to form a heat insulating layer (expansion layer). This heat insulating layer blocks heat from the battery cell in a high temperature state, suppressing heat transfer to other battery cells, and reduces the adhesion between the battery cell and the cooling plate, thereby improving the heat insulation property.
[0019] <Modified polyolefin resin (A)> The modified polyolefin resin (A) is a resin in which at least one of the main chain terminals and the side chains of an unmodified polyolefin resin has been modified. The modification position is not particularly limited.
[0020] Specific examples of unmodified polyolefin resins include ethylene homopolymers such as low-density polyethylene (LDPE) and high-density polyethylene (HDPE), ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-hexene copolymers, ethylene-octene copolymers, ethylene-propylene-butene copolymers, ethylene-propylene-hexene copolymers, ethylene-propylene-octene copolymers, ethylene-butene-hexene copolymers, ethylene-butene-octene copolymers, ethylene-hexene-octene copolymers, and other ethylene-α-olefin copolymers, ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, and ethylene-methyl(meth)acrylate copolymers. copolymers, ethylene-based copolymers such as ethylene-ethyl (meth)acrylate copolymers, and ethylene-(meth)acrylic acid-methyl (meth)acrylate copolymers; propylene homopolymers, propylene-ethylene random copolymers, propylene-butene random copolymers, propylene-ethylene-hexene random copolymers, propylene-ethylene-octene random copolymers, propylene-butene-hexene random copolymers, propylene-butene-octene random copolymers, propylene-hexene-octene random copolymers, and propylene-ethylene block copolymers; butene homopolymers and butene copolymers. Hereinafter, the general term for polymers and copolymers may be referred to as "(co)polymers." "(Meth)acrylic acid" means acrylic acid and / or methacrylic acid. Hereinafter, the same applies.
[0021] The above-mentioned ethylene-based copolymer, propylene-based copolymer, and butene-based copolymer respectively mean copolymers containing ethylene, propylene, or butene in a proportion of 50 mol % or more of all monomer units constituting the copolymer. These raw material polyolefin resins may be used alone or in any combination and ratio of two or more kinds.
[0022] Among these, from the viewpoint of recyclability, propylene-based copolymers such as propylene homopolymer, propylene-ethylene random copolymer, propylene-butene random copolymer, propylene-ethylene-hexene random copolymer, propylene-ethylene-octene random copolymer, propylene-butene-hexene random copolymer, propylene-butene-octene random copolymer, propylene-hexene-octene random copolymer, and propylene-ethylene block copolymer are preferred.
[0023] The density of the raw material polyolefin resin (JIS K7112-1) is not particularly limited, but is preferably 0.85 g / cm 3 More preferably, it is 0.87 g / cm 3 On the other hand, 0.98 g / cm 3 Preferably less than 0.97 g / cm 3 The following is the result. The melt flow rate (MFR) of the raw material polyolefin resin is not particularly limited, but from the viewpoint of moldability, it is preferably 0.01 g / 10 min to 50 g / 10 min, more preferably 0.1 g / 10 min to 30 g / 10 min. Here, the MFR of the polyolefin resin means the value at 190° C. and a load of 2.16 kg when the polyolefin resin is an ethylene (co)polymer or a butene (co)polymer, and means the value at 230° C. and a load of 2.16 kg when the polyolefin resin is a propylene (co)polymer.
[0024] The modified polyolefin resin (A) contained in the present resin composition is obtained by introducing a modifying group into the unmodified polyolefin resin. The modifying group is not particularly limited, but is preferably at least one functional group selected from the group consisting of an acid anhydride group, a carboxyl group, an amino group, an imino group, an alkoxysilyl group, a silanol group, a silyl ether group, a hydroxyl group, and an epoxy group. Among them, polyolefin resins modified with at least one selected from the group consisting of unsaturated carboxylic acids and their derivatives, and unsaturated silanes are preferred, and polyolefin resins graft-modified with unsaturated carboxylic acids and / or their derivatives are more preferred. "Graft-modified" means that unsaturated carboxylic acids and / or their derivatives are bonded to a polyolefin resin. As described above, the modification position of the unmodified polyolefin resin is not particularly limited, and it is sufficient that at least one of the main chain terminal and the side chain of the polyolefin resin is modified.
[0025] Examples of unsaturated carboxylic acids used for graft modification of unmodified polyolefin resins include acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid, which may be used alone or in combination. Examples of derivatives of unsaturated carboxylic acids include acid anhydrides, esters, amides, imides, and metal salts, which may be used alone or in combination.
[0026] Specific examples of the derivative of an unsaturated carboxylic acid include maleic anhydride, himic anhydride, itaconic anhydride, citraconic anhydride, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl acrylate, maleic acid monoethyl ester, maleic acid diethyl ester, itaconic acid monomethyl ester, itaconic acid diethyl ester, acrylamide, methacrylamide, maleic acid monoamide, maleic acid diamide, maleic acid-N-monoethylamide, maleic acid-N,N-diethylamide, maleic acid-N,N-monobutylamide, maleic acid-N,N-dibutylamide, fumaric acid monoamide, fumaric acid diamide, fumaric acid-N-monobutylamide, fumaric acid-N,N-dibutylamide, maleimide, N-butylmaleimide, N-phenylmaleimide, sodium acrylate, sodium methacrylate, potassium acrylate, and potassium methacrylate.
[0027] The unsaturated carboxylic acid and / or its derivative may be used alone or in any combination of two or more in any ratio. Of these, maleic acid or its anhydride is particularly preferred because of its low electron density and high reactivity.
[0028] The density of the modified polyolefin resin (A) is not particularly limited, but the density measured according to JIS K7112-1 is preferably 0.85 g / cm. 3 More preferably, 0.87 g / cm 3 or more, while preferably 0.98 g / cm 3 Less than or equal to 0.97 g / cm 3 The following is the result.
[0029] The melt flow rate (MFR) of the modified polyolefin resin (A) is not particularly limited, but is preferably 0.01 g / 10 min to 1000 g / 10 min, more preferably 0.1 g / 10 min to 500 g / 10 min. The MFR of the modified polyolefin resin (A) means a value at 190 ° C. and a load of 2.16 kg when the raw polyolefin resin is an ethylene (co)polymer or a butene (co)polymer. When the raw polyolefin resin is a propylene (co)polymer, a value at 230 ° C., a load of 2.16 kg, and a 2 mm orifice may be used, but when the molecular weight of the modified polyolefin resin (A) is low and measurement is difficult, it may be measured under the conditions of 180 ° C., a load of 2.16 kg, and a 1 mm orifice.
[0030] The melting point of the modified polyolefin resin (A) is preferably 170°C or less, more preferably 165°C or less, and even more preferably 160°C or less. When the melting point of the modified polyolefin resin (A) is 170°C or less, the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) described below expand in a molten state of the resin, and the foaming agent (excluding the thermally expandable foaming agent (Bb) described below) foams, so that better dismantling properties and heat insulation properties can be obtained. The melting point of the modified polyolefin resin (A) can be measured by a differential scanning calorimeter in accordance with JIS K 7121.
[0031] Hereinafter, a method for producing the graft-modified polyolefin resin out of the modified polyolefin resins (A) will be described. Graft modification of raw polyolefin resin (unmodified polyolefin resin) can be carried out by various conventionally known methods. The modification method includes, but is not limited to, a melt modification method in which an unsaturated carboxylic acid and / or its derivative is added to a molten raw polyolefin resin to perform graft copolymerization, and a solution modification method in which an unsaturated carboxylic acid and / or its derivative is added to a raw polyolefin resin dissolved in a solvent to perform graft copolymerization. Among these, from the viewpoint of hygiene, the melt modification method, which does not require the use of a solvent, is preferred, and the graft modification using an extruder is more preferred. For efficient graft modification, it is preferred to carry out the modification in the presence of a radical initiator.
[0032] The radical initiator is not particularly limited, but is preferably an organic peroxide or an azo compound, and more preferably an organic peroxide. Specifically, dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, 1,4-bis(t-butylperoxyisopropyl)benzene, 1,1-bis(t-butylperoxy)cyclohexane, n-butyl-4,4-bis(t-butylperoxy)valerate, 2,2-bis(4,4-t-butylperoxycyclohexyl)propane, 2,2-bis(t-butylperoxy)butane, and 1,1-bis(t-butylperoxy)cyclododecane; t-butylperoxyacetate, t-butylperoxy-2-ethylhexanoate, t-butylperoxypivalate, t-butylperoxylaurate, t-butylperoxybenzoate, t-butylperoxyisopropyl peroxy esters such as diethyl carbonate, t-butyl peroxymaleic acid, di-t-butyl peroxy isophthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)hexyne-3, and 2,5-dimethyl-2,5-di(toluylperoxy)hexane; diacyl peroxides such as di-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, and dibenzoyl peroxide; hydroperoxides such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, and 2,5-dimethyl-2,5-di(hydroperoxy)hexane; and ketone peroxides such as methyl ethyl ketone peroxide and cyclohexanone peroxide, but are not particularly limited thereto.
[0033] Among them, a radical initiator having a decomposition temperature of 100° C. or more, at which the half-life is 1 minute, is preferred from the viewpoint of graft modification efficiency. Specifically, dialkyl peroxides such as di-t-butyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3, and peroxy esters such as t-butyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexyne-3 are preferred.
[0034] The radical initiator may be used alone or in any combination and ratio of two or more. The amount of the radical initiator used is not particularly limited, but is preferably 0.001 to 5 parts by mass per 100 parts by mass of the raw material polyolefin resin.
[0035] The content of the unsaturated carboxylic acid and / or its derivative in the modified polyolefin resin (A) (hereinafter sometimes referred to as the graft rate) varies depending on the type of raw material polyolefin resin and the unsaturated carboxylic acid and / or its derivative used for modification, and is not particularly limited, but is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, relative to the total amount of the modified polyolefin resin (A), and is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less. When the graft rate is equal to or greater than the lower limit of the above-mentioned preferred value, the adhesiveness and thermal conductivity of the resin composition become good. On the other hand, when the graft rate is equal to or less than the upper limit of the above-mentioned preferred value, it is possible to prevent partial crosslinking of the raw material polyolefin resin itself during grafting, which would result in a decrease in moldability, and to prevent deterioration of the product appearance due to the generation of fish eyes or foreign matter.
[0036] The graft ratio can be measured by press-molding the modified polyolefin resin (A) into a sheet having a thickness of 100 μm to prepare a test sample, and using an infrared absorption spectroscopy to determine the graft ratio from the absorption characteristic of the carboxylic acid and / or its derivative in the resin. -1 It can be determined by measuring the carbonyl characteristic absorption (C=O stretching vibration band). In the graft modification of the raw material polyolefin resin, unsaturated carboxylic acid and / or its derivative that has not reacted with the raw material polyolefin resin may remain, but the graft ratio in this specification means the value obtained when the modified polyolefin resin (A) is measured by the above-mentioned method, as described above.
[0037] The modified polyolefin resin (A) suitable for the present invention may be a commercially available product. For example, a product having the above-mentioned properties may be appropriately selected from the "Modic (registered trademark)" series manufactured by Mitsubishi Chemical Corporation.
[0038] The proportion of the modified polyolefin resin (A) relative to the total mass of the resin composition is preferably 1 mass% or more, more preferably 2 mass% or more, and even more preferably 3 mass% or more, and is preferably 95 mass% or less, more preferably 93 mass% or less, and even more preferably 90 mass% or less. When the proportion of the modified polyolefin resin (A) is equal to or more than the lower limit, the adhesiveness and thermal conductivity are excellent, and when it is equal to or less than the upper limit, the contents of the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) described later in the resin composition can be ensured. The proportion of the modified polyolefin resin (A) relative to the total mass of the present resin composition may be, for example, 1 mass% or more and 95 mass% or less, 2 mass% or more and 93 mass% or less, or 3 mass% or more and 90 mass% or less.
[0039] <Thermal expansion material (B)> Examples of the thermally expandable material (B) include the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) described below, and it is preferable that the thermally expandable material (B) contains the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb).
[0040] <Thermal expansion flame retardant (Ba)> The thermally expandable flame retardant (Ba) is not particularly limited as long as it is a flame retardant that has the property of expanding by heating. For example, there is one that imparts flame retardancy by forming a carbonized coating during combustion, and the coating expands to form an expansion layer. From the viewpoint of improving flame-shielding properties, it is preferable to include a phosphorus-based flame retardant as the thermally expandable flame retardant. On the other hand, in the classification focusing on the action mechanism of the flame retardant, it is preferable to include an intumescent flame retardant as the thermally expandable flame retardant from the viewpoint of improving flame-shielding properties. The intumescent flame retardant is a flame retardant that suppresses the combustion of a material by forming a surface expansion layer (intemescent) that prevents the diffusion of radiant heat from the combustion source and combustion gases and smoke from the combustion material to the outside. From the viewpoint of environmental friendliness, it is preferable to use a non-halogen flame retardant.
[0041] Phosphorus-based flame retardants are phosphorus compounds, i.e. compounds that contain phosphorus atoms in their molecules. Phosphorus-based flame retardants exert their flame retardant effect by forming char (carbonized film) when an adhesive sheet containing an easily dismantlable adhesive material is burned. The phosphorus-based flame retardant may be a known one, and examples thereof include (poly)phosphates, (poly)phosphate esters, etc. Here, "(poly)phosphates" refers to phosphates or polyphosphates, and "(poly)phosphate esters" refers to phosphate esters or polyphosphate esters. It is preferable that the phosphorus-based flame retardant is a solid at 80°C.
[0042] As the phosphorus-based flame retardant, (poly)phosphates are preferred in terms of flame retardancy. Examples of the (poly)phosphate include salts of (poly)phosphoric acid and nitrogen compounds, such as ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, piperazine orthophosphate, ammonium pyrophosphate, melamine pyrophosphate, piperazine pyrophosphate, melamine orthophosphate, calcium phosphate, and magnesium phosphate. Examples of the nitrogen compounds include ammonia, melamine, piperazine, and other nitrogen compounds. Examples of the other nitrogen compounds include, for example, N,N,N',N'-tetramethyldiaminomethane, ethylenediamine, N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-diethylethylenediamine, Amines, 1,2-propanediamine, 1,3-propanediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, trans-2,5-dimethylpiperazine, 1,4-bis(2-aminoethyl)piperazine, 1,4-bis(3-aminopropyl)piperazine, acetoguanamine, benzoguanamine, acryloylguanamine amine, 2,4-diamino-6-nonyl-1,3,5-triazine, 2,4-diamino-6-hydroxy-1,3,5-triazine, 2-amino-4,6-dihydroxy-1,3,5-triazine, 2,4-diamino-6-methoxy-1,3,5-triazine, 2,4-diamino-6-ethoxy-1,3,5-triazine, 2,4-diamino-6-propoxy-1,3,5-triazine, 2,4-diamino-6-isopropoxy-1,3,5-triazine, 2 ,4-diamino-6-mercapto-1,3,5-triazine, 2-amino-4,6-dimercapto-1,3,5-triazine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, 1,3-hexylenedimelamine, etc.
[0043] The thermally expandable flame retardant (Ba) preferably contains a compound having a melamine structure or a piperazine structure. The thermally expandable flame retardant (Ba) may be, for example, a mixture containing a compound having a melamine structure and a compound having a piperazine structure. The thermally expandable flame retardants (Ba) may be used alone or in combination of two or more.
[0044] Commercially available thermally expandable flame retardants (Ba) include, for example, Adeka STAB FP-2100J, FP-2200, and FP-2500S (manufactured by ADEKA CORPORATION).
[0045] In the present resin composition, the proportion of the thermally expandable flame retardant (Ba) is preferably 10 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the total mass of the modified polyolefin-based resin (A) of the present resin composition and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary. When the ratio of the thermally expandable flame retardant (Ba) to the total mass of the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary is within the above range, when the resin composition is used in combination with the copolymer (C) of an α-olefin and an unsaturated carboxylic acid described below, a significant decrease in the mechanical properties of the molded body obtained by molding the resin composition can be prevented and high flame retardancy can be obtained. However, the total mass of the modified polyolefin-based resin (A) and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary in the resin composition means the content of component (A) when the resin composition does not contain component (D) and component (E); means the total mass of component (A) + component (D) or component (E) contained when the resin composition contains either component (D) or component (E); and means the total mass of component (A) + component (D) + component (E) when the resin composition contains component (D) and component (E) (the same applies hereinafter). It should be noted that the polyethylene resin (D) and the polypropylene resin (E) are unmodified resins and do not fall under the category of the modified polyolefin resin (A).
[0046] In particular, the proportion of the thermally expandable flame retardant (Ba) relative to 100 parts by mass of the total mass of the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 45 parts by mass or more, still more preferably 55 parts by mass or more, while being preferably 90 parts by mass or less, more preferably 80 parts by mass or less, even more preferably 75 parts by mass or less, still more preferably 70 parts by mass or less. The ratio of the thermally expandable flame retardant (Ba) to 100 parts by mass of the total mass of the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary may be, for example, 20 parts by mass or more and 90 parts by mass or less, 40 parts by mass or more and 80 parts by mass or less, 45 parts by mass or more and 75 parts by mass or less, or 55 parts by mass or more and 70 parts by mass or less.
[0047] The proportion of the thermally expandable flame retardant (Ba) relative to the total mass of the resin composition is preferably 15% by mass or more, more preferably 25% by mass or more, and even more preferably 35% by mass or more, and is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. If the proportion of the thermally expandable flame retardant (Ba) is equal to or more than the lower limit, the flame retardancy is excellent, and dismantling properties and heat insulation properties can be improved. If the proportion is equal to or less than the upper limit, the inherent physical properties of the modified polyolefin resin (A) contained in the resin composition and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary are easily expressed. The proportion of the thermally expandable flame retardant (Ba) relative to the total mass of the present resin composition may be, for example, 15 mass% or more and 70 mass% or less, 25 mass% or more and 60 mass% or less, or 35 mass% or more and 50 mass% or less.
[0048] <Thermal expansion foaming agent (Bb)> The thermally expandable foaming agent (Bb) is not particularly limited as long as it is a foaming agent that has the property of expanding by heating, and for example, one containing a chemical foaming agent and / or a physical foaming agent and a thermoplastic resin capsule that encapsulates them can be suitably used. The thermally expandable foaming agent (Bb) containing a chemical foaming agent and / or a physical foaming agent and a thermoplastic resin capsule that encapsulates them contains a foaming agent inside the thermoplastic resin, so that when heated, the shell resin softens and the pressure of the foaming agent present inside increases, and the foaming agent expands in volume suddenly.
[0049] Examples of chemical foaming agents include azodicarbonamide (ADCA), N,N'-dinitropentamethylenetetramine (DPT), and 4,4'-oxybisbenzenesulfonylhydrazide (OBSH). An example of a physical foaming agent is a hydrocarbon compound having a relatively low boiling point. Among them, the thermally expandable foaming agent (Bb) is preferably one containing a physical foaming agent and a thermoplastic resin capsule that encapsulates the physical foaming agent, and more preferably one containing a physical foaming agent containing a hydrocarbon compound and a thermoplastic resin capsule that encapsulates the physical foaming agent.
[0050] As the thermally expandable foaming agent (Bb), commercially available products can be used, such as "Matsumoto Microsphere" (manufactured by Matsumoto Yushi Seiyaku Co., Ltd.), "EXPANCEL" (manufactured by Nippon Phillite Co., Ltd.), "Advancell EM Series" (manufactured by Sekisui Chemical Co., Ltd.), and "Microsphere" (manufactured by Kureha Corporation).
[0051] In the present resin composition, the proportion of the thermally expandable foaming agent (Bb) is preferably 1 part by mass or more and 20 parts by mass or less per 100 parts by mass of the total mass of the modified polyolefin-based resin (A) of the present resin composition and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary. When the ratio of the thermally expandable foaming agent (Bb) to the total mass of the modified polyolefin-based resin (A) and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary is within this range, the inherent physical properties of the modified polyolefin-based resin (A) and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary contained in the resin composition are easily expressed while maintaining dismantling ability and heat insulation.
[0052] In particular, the ratio of the thermally expandable foaming agent (Bb) to 100 parts by mass of the total mass of the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, while being preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less. The ratio of the thermally expandable foaming agent (Bb) to 100 parts by mass of the total mass of the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary may be, for example, 1 part by mass or more and 20 parts by mass or less, 3 parts by mass or more and 15 parts by mass or less, or 5 parts by mass or more and 10 parts by mass or less.
[0053] The proportion of the thermally expandable foaming agent (Bb) relative to the total mass of the present resin composition is preferably 1 mass% or more, more preferably 3 mass% or more, and even more preferably 4 mass% or more, and is preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, and particularly preferably 7 mass% or less. If the proportion of the thermally expandable foaming agent (Bb) is equal to or more than the lower limit, dismantling properties and heat insulation properties can be improved, and if it is equal to or less than the upper limit, the inherent physical properties of the modified polyolefin resin (A) contained in the present resin composition and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary are easily expressed. The proportion of the thermally expandable foaming agent (Bb) relative to the total mass of the present resin composition may be, for example, 1 mass% or more and 20 mass% or less, 3 mass% or more and 15 mass% or less, 3 mass% or more and 10 mass% or less, or 4 mass% or more and 7 mass% or less.
[0054] The present resin composition may contain the above-mentioned thermally expandable flame retardant (Ba) and the above-mentioned thermally expandable foaming agent (Bb) in combination.
[0055] <Copolymer of α-olefin and unsaturated carboxylic acid (C)> The copolymer (C) enhances the dispersibility of the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) in the modified polyolefin-based resin (A) and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary. In the present invention, "copolymer (C) of α-olefin and unsaturated carboxylic acid" (hereinafter sometimes simply referred to as "copolymer") means a copolymer in which the ratio of α-olefin units to the total of 100 mol% of α-olefin units and unsaturated carboxylic acid units is 20 mol% or more and 80 mol% or less. In the copolymer (C), the ratio of the α-olefin units to the total of 100 mol% of the α-olefin units and the unsaturated carboxylic acid units is preferably 30 mol% or more, and preferably 70 mol% or less. If the ratio of the α-olefin units is equal to or more than the lower limit, the compatibility with the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as required is superior, and if the ratio is equal to or less than the upper limit, the compatibility with the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) is superior.
[0056] In the copolymer (C), the α-olefin is preferably an α-olefin having 10 to 80 carbon atoms. If the α-olefin has 10 or more carbon atoms, it tends to have better compatibility with the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary. On the other hand, if the α-olefin has 80 or less carbon atoms, it tends to be more advantageous in terms of raw material costs. The number of carbon atoms of the α-olefin is more preferably 12 to 70, even more preferably 15 to 65, and particularly preferably 18 to 60.
[0057] In the copolymer (C), examples of the unsaturated carboxylic acid include (meth)acrylic acid, maleic acid, methylmaleic acid, fumaric acid, methylfumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, glutaconic acid, norbornane-5-ene-2,3-dicarboxylic acid, and esters, anhydrides, imides, etc. of these unsaturated carboxylic acids. "(Meth)acrylic acid" refers to acrylic acid or methacrylic acid. Specific examples of the ester, anhydride or imide of an unsaturated carboxylic acid include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and glycidyl (meth)acrylate; dicarboxylic acid anhydrides such as maleic anhydride, itaconic anhydride, citraconic anhydride, and 5-norbornene-2,3-dicarboxylic acid anhydride; and maleimide compounds such as maleimide, N-ethylmaleimide, and N-phenylmaleimide. These may be used alone or in combination of two or more.
[0058] Among the above, esters and dicarboxylic anhydrides are preferred from the viewpoint of copolymerization reactivity, and among them, dicarboxylic anhydrides are preferred from the viewpoint of compatibility with the thermally expandable flame retardant (Ba) and the thermally expandable blowing agent (Bb), and maleic anhydride is particularly preferred.
[0059] The weight average molecular weight of the copolymer (C) is preferably 2,000 or more, more preferably 3,000 or more, and even more preferably 5,000 or more, and is preferably 50,000 or less, more preferably 30,000 or less, and more preferably 10,000 or less. When the weight average molecular weight of the copolymer (C) is within the above upper and lower limit ranges, the dispersibility of the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) is further improved. The weight average molecular weight of the copolymer (C) may be, for example, 2,000 or more and 50,000 or less, 3,000 or more and 30,000 or less, or 5,000 or more and 10,000 or less. The weight average molecular weight of the copolymer (C) is a value calculated as standard polystyrene by dissolving the copolymer (C) in tetrahydrofuran (THF) and measuring the molecular weight by gel permeation chromatography.
[0060] Commercially available copolymers (C) include, for example, Ricorb CE2 (Clariant Japan Co., Ltd.) and Diacalna 30M (Mitsubishi Chemical Co., Ltd.). The copolymer (C) is not the above-mentioned modified polyolefin resin (A).
[0061] When the resin composition contains the thermally expandable flame retardant (Ba), as described above, the resin composition contains the copolymer (C), and the ratio of the copolymer (C) to the thermally expandable flame retardant (Ba) (100 mass%) is preferably 10 mass% or less. In particular, the proportion of the copolymer (C) relative to the thermally expandable flame retardant (Ba) (100 mass%) is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, still more preferably 0.5 mass% or more, even more preferably 1 mass% or more, particularly preferably 3 mass% or more, while more preferably 8 mass% or less, still more preferably 7 mass% or less, still more preferably 6 mass% or less, particularly preferably 5 mass% or less. By setting the ratio of the copolymer (C) to the thermally expandable flame retardant (Ba) (100% by mass) within the above range, it is possible to obtain a molded article that has high flame retardancy, dismantling properties and heat insulation properties while maintaining high mechanical strength.
[0062] In the present resin composition, the ratio of the copolymer (C) to the thermally expandable flame retardant (Ba) (100 mass%) may be, for example, 0.01 mass% or more and 8 mass% or less, 0.05 mass% or more and 8 mass% or less, 0.1 mass% or more and 7 mass% or less, 0.1 mass% or more and 6 mass% or less, 0.5 mass% or more and 6 mass% or less, 1 mass% or more and 6 mass% or less, or 3 mass% or more and 5 mass% or less.
[0063] When the resin composition contains the thermally expandable flame retardant (Ba), the proportion of the copolymer (C) relative to the total mass of the resin composition is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, and even more preferably 1 mass% or more, while it is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 3 mass% or less. When the proportion of the copolymer (C) is equal to or greater than the lower limit, the thermally expandable flame retardant (Ba) is well dispersed, and the flame retardancy of the resin composition, as well as the dismantling property, heat insulating property, and appearance of the obtained molded article, are improved. When the proportion of the copolymer (C) is equal to or less than the upper limit, the influence of the copolymer (C) on the flame retardancy of the resin composition can be suppressed. The proportion of the copolymer (C) relative to the total mass of the present resin composition may be, for example, 0.01 mass% or more and 10 mass% or less, 0.1 mass% or more and 5 mass% or less, or 1 mass% or more and 3 mass% or less.
[0064] When the resin composition contains a thermally expandable flame retardant (Ba), the proportion of the copolymer (C) relative to the total mass (100 mass%) of the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary, and the thermally expandable flame retardant (Ba) in the resin composition is preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 1 mass% or more, and still more preferably 1.5 mass% or more, while being preferably 5 mass% or less, more preferably 4 mass% or less, and even more preferably 3 mass% or less. If the proportion of copolymer (C) is equal to or greater than the lower limit, the thermally expandable flame retardant (Ba) is better dispersed, and the flame retardancy of the resin composition, as well as the dismantling property, heat insulating property, and appearance of the obtained molded article, are improved. If the proportion of copolymer (C) is equal to or less than the upper limit, the influence of copolymer (C) on the flame retardancy of the resin composition can be further suppressed.
[0065] The ratio of the copolymer (C) to the total mass of the modified polyolefin resin (A), the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary, and the thermally expandable flame retardant (Ba) may be, for example, 0.01 mass% or more and 10 mass% or less, 0.01 mass% or more and 5 mass% or less, 0.1 mass% or more and 4 mass% or less, 1 mass% or more and 3 mass% or less, or 1.5 mass% or more and 3 mass% or less.
[0066] When the present resin composition contains a thermally expandable foaming agent (Bb), as described above, the present resin composition contains the copolymer (C), and the ratio of the copolymer (C) to the thermally expandable foaming agent (Bb) (100 mass%) is preferably 30 mass% or less. In particular, the proportion of the copolymer (C) relative to the thermally expandable foaming agent (Bb) (100 mass%) is preferably 0.03 mass% or more, more preferably 0.3 mass% or more, even more preferably 0.5 mass% or more, still more preferably 1 mass% or more, even more preferably 2 mass% or more, particularly preferably 3 mass% or more, while more preferably 30 mass% or less, still more preferably 20 mass% or less, still more preferably 15 mass% or less, particularly preferably 10 mass% or less. By using the copolymer (C) in the above-mentioned range relative to the thermally expandable foaming agent (Bb) (100% by mass), it is possible to obtain a molded article having dismantling properties and heat insulating properties while maintaining high mechanical strength.
[0067] In the present resin composition, the ratio of the copolymer (C) to the thermally expandable foaming agent (Bb) (100 mass%) may be, for example, 0.03 mass% or more and 30 mass% or less, 0.3 mass% or more and 30 mass% or less, 0.5 mass% or more and 30 mass% or less, 1 mass% or more and 20 mass% or less, 2 mass% or more and 15 mass% or less, or 3 mass% or more and 10 mass% or less.
[0068] When the resin composition contains a thermally expandable foaming agent (Bb), the proportion of the copolymer (C) relative to the total mass of the resin composition is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.3 mass% or more, while it is preferably 3 mass% or less, more preferably 2 mass% or less, and even more preferably 1 mass% or less. When the proportion of the copolymer (C) is equal to or greater than the lower limit, the thermally expandable foaming agent (Bb) disperses well, and the dismantling property, heat insulation property, and appearance of the obtained molded article are good. When the proportion of the copolymer (C) is equal to or less than the upper limit, the influence of the copolymer (C) on the adhesive properties of the resin composition can be further suppressed. The proportion of the copolymer (C) relative to the total mass of the present resin composition may be, for example, 0.1 mass% or more and 3 mass% or less, 0.2 mass% or more and 2 mass% or less, or 0.3 mass% or more and 1 mass% or less.
[0069] When the present resin composition contains a thermally expandable foaming agent (Bb), the proportion of the copolymer (C) relative to the total mass (100 mass%) of the modified polyolefin-based resin (A) and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary, and the thermally expandable foaming agent (Bb) in the present resin composition is preferably 0.05 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.2 mass% or more, and still more preferably 0.3 mass% or more, while being preferably 3 mass% or less, more preferably 2 mass% or less, and even more preferably 1 mass% or less. When the proportion of the copolymer (C) is equal to or greater than the lower limit, the thermally expandable foaming agent (Bb) is more easily dispersed, and the dismantling property, heat insulation property, and appearance of the obtained molded article are improved. When the proportion of the copolymer (C) is equal to or less than the upper limit, the influence of the copolymer (C) on the adhesive properties of the resin composition can be more suppressed.
[0070] The ratio of the copolymer (C) to the total mass of the modified polyolefin resin (A), the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary, and the thermally expandable foaming agent (Bb) may be, for example, 0.05 mass% or more and 5 mass% or less, 0.1 mass% or more and 3 mass% or less, 0.2 mass% or more and 2 mass% or less, or 0.3 mass% or more and 1 mass% or less.
[0071] The ratio of the total mass of the modified polyolefin resin (A), the thermally expandable flame retardant (Ba) or the thermally expandable foaming agent (Bb), and the copolymer (C) to the total mass of the resin composition is preferably 30% by mass or more, more preferably 35% by mass or more, even more preferably 40% by mass or more, particularly preferably 45% by mass or more, and may be 100% by mass. For example, when the total mass of the component (A), the component (B) (meaning the above-mentioned thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb)) and the component (C) is 100% by mass, the modified polyolefin resin (A), the thermally expandable flame retardant (Ba) or the thermally expandable foaming agent (Bb), and the copolymer (C) can be appropriately selected within the above-mentioned range of amounts that can be taken so that the total of the three components is 100% by mass.
[0072] <Polyethylene resin (D)> The resin composition may further contain a polyethylene resin (D). By containing the polyethylene resin (D), the composition can be adhered to an adherend at a lower temperature, and the moldability of the resin composition when processed into a film or sheet shape is improved. The polyethylene resin (D) is an unmodified resin, an unmodified polyethylene resin, and does not fall under the modified polyolefin resin (A).
[0073] The polyethylene resin (D) is not particularly limited, but may be a homopolymer of ethylene or a copolymer of ethylene and another monomer, and examples of the other monomer include α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 4,4-dimethyl-1-pentene, 1-hexene, 4-methyl-1-hexene, 1-heptene, 1-octene, 1-decene, and 1-octadecene, as well as vinyl acetate, vinyl alcohol, (meth)acrylic acid, and (meth)acrylic acid esters. Here, (meth)acrylic acid means acrylic acid and / or methacrylic acid (hereinafter the same).
[0074] Specific examples of the polyethylene resin (D) are the same as those listed as specific examples of the unmodified polyolefin resin.Specific examples include ethylene homopolymers such as low-density polyethylene (LDPE) and high-density polyethylene (HDPE), ethylene-propylene copolymers, ethylene-butene copolymers, ethylene-hexene copolymers, ethylene-octene copolymers, ethylene-propylene-butene copolymers, ethylene-propylene-hexene copolymers, ethylene-propylene-octene copolymers, ethylene-butene-hexene copolymers, ethylene-butene-octene copolymers, ethylene-hexene-octene copolymers, and ethylene-α-olefin copolymers such as ethylene-vinyl acetate copolymers, ethylene-(meth)acrylic acid copolymers, ethylene-methyl(meth)acrylate copolymers, ethylene-ethyl(meth)acrylate copolymers, and ethylene-(meth)acrylic acid-methyl(meth)acrylate copolymers.Here, "(co)polymer" is a general term for polymers and copolymers (hereinafter the same). Here, the ethylene-based copolymer means a copolymer containing ethylene in the largest amount among all monomer units constituting the copolymer, and preferably a copolymer containing ethylene in a proportion of more than 50 mol %. These polyethylene resins (D) may be used alone or in any combination and ratio of two or more kinds.
[0075] Among these, as the polyethylene-based resin (D), ethylene homopolymers, ethylene-α-olefin copolymers, and ethylene-vinyl acetate copolymers, which are ethylene-based (co)polymers, are preferred because they are inexpensive and easily available and are therefore economically advantageous, and from the viewpoint of improving processability, low-density polyethylene and ethylene-α-olefin copolymers are more preferred.
[0076] When the resin composition contains a polyethylene-based resin (D), the proportion of the polyethylene-based resin (D) relative to the total mass of the resin composition is preferably 0.5 mass% or more, more preferably 1.0 mass% or more, and even more preferably 1.5 mass% or more, while it is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less. When the proportion of the polyethylene resin (D) is equal to or greater than the lower limit, the film formability can be improved. In particular, neck-in is reduced. When the proportion of the polyethylene resin (D) is equal to or less than the upper limit, the heat resistance is maintained. The proportion of the polyethylene resin (D) relative to the total mass of the present resin composition may be, for example, 0.5 mass% or more and 20 mass% or less, 1.0 mass% or more and 10 mass% or less, or 1.5 mass% or more and 5 mass% or less.
[0077] When the resin composition contains a polyethylene-based resin (D), the ratio of the total mass of the modified polyolefin-based resin (A) and the polyethylene-based resin (D) to the total mass of the resin composition is preferably 2 mass% or more, more preferably 3 mass% or more, even more preferably 4 mass% or more, still more preferably 5 mass% or more, and on the other hand, is preferably 98 mass% or less, more preferably 97 mass% or less, even more preferably 96 mass% or less, and still more preferably 95 mass% or less. When the total mass ratio of the modified polyolefin resin (A) and the polyethylene resin (D) is equal to or greater than the lower limit, both the adhesive strength before heating and the film formability can be achieved. When the total mass ratio of the modified polyolefin resin (A) and the polyethylene resin (D) is equal to or less than the upper limit, the adhesiveness to a resin battery case is excellent.
[0078] The total mass ratio of the modified polyolefin resin (A) and the polyethylene resin (D) may be, for example, 2 mass% or more and 98 mass% or less, 3 mass% or more and 97 mass% or less, 4 mass% or more and 96 mass% or less, or 5 mass% or more and 95 mass% or less.
[0079] <Polypropylene resin (E)> The resin composition may further contain a polypropylene-based resin (E). By containing the polypropylene-based resin (E), the resin composition has excellent adhesion to a resin battery case, particularly a polypropylene battery case. It also contributes to improving heat resistance and mechanical strength. Note that the polypropylene-based resin (E) is an unmodified resin, an unmodified polypropylene-based resin, and does not fall under the modified polyolefin-based resin (A).
[0080] The polypropylene resin (E) is not particularly limited, but examples thereof include homopolymers of propylene and copolymers of propylene and other monomers. Examples of the other monomers include α-olefins having 3 to 20 carbon atoms, such as ethylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 4,4-dimethyl-1-pentene, 1-hexene, 4-methyl-1-hexene, 1-heptene, 1-octene, 1-decene, and 1-octadecene.
[0081] Specific examples of the polypropylene-based resin (E) are the same as those listed as specific examples of the unmodified polyolefin-based resin.Specific examples include propylene homopolymers, propylene-ethylene random copolymers, propylene-butene random copolymers, propylene-ethylene-hexene random copolymers, propylene-ethylene-octene random copolymers, propylene-butene-hexene random copolymers, propylene-butene-octene random copolymers, propylene-hexene-octene random copolymers, and propylene-ethylene block copolymers.Here, "(co)polymer" is a general term for polymers and copolymers (hereinafter the same). Here, the propylene-based copolymer means a copolymer containing propylene in the largest amount among all monomer units constituting the copolymer, and preferably a copolymer containing propylene in a proportion of more than 50 mol %. These polypropylene resins (E) may be used alone or in any combination and ratio of two or more kinds.
[0082] Among these, as the polypropylene-based resin (E), propylene-based (co)polymers such as propylene homopolymer, propylene-ethylene random copolymer, and propylene-ethylene-butene copolymer are preferred because they are inexpensive and easily available and are economically advantageous, and from the viewpoints of adhesion to a resin battery case and mechanical properties, propylene homopolymer and propylene-ethylene random copolymer are more preferred.
[0083] When the resin composition contains a polypropylene-based resin (E), the proportion of the polypropylene-based resin (E) relative to the total mass of the resin composition is preferably 10 mass% or more, more preferably 20 mass% or more, and even more preferably 30 mass% or more, while it is preferably 95 mass% or less, more preferably 90 mass% or less, and even more preferably 85 mass% or less. When the proportion of the polypropylene-based resin (E) is equal to or greater than the lower limit, the heat resistance, moldability, and adhesion to a resin battery case are excellent. When the proportion of the polypropylene-based resin (E) is equal to or less than the upper limit, the peelability and adhesion to a metal plate are excellent. The proportion of the polypropylene resin (E) relative to the total mass of the present resin composition may be, for example, 10% by mass or more and 95% by mass or less, 20% by mass or more and 90% by mass or less, or 30% by mass or more and 85% by mass or less.
[0084] When the resin composition contains a polypropylene-based resin (E), the ratio of the total mass of the modified polyolefin-based resin (A) and the polypropylene-based resin (E) to the total mass of the resin composition is preferably 10 mass% or more, more preferably 20 mass% or more, even more preferably 30 mass% or more, still more preferably 40 mass% or more, while being preferably 98 mass% or less, more preferably 97 mass% or less, even more preferably 96 mass% or less, and still more preferably 95 mass% or less. When the total mass ratio of the modified polyolefin resin (A) and the polypropylene resin (E) is equal to or greater than the lower limit, the adhesiveness to both the resin battery case and the metal plate is excellent. When the total mass ratio of the modified polyolefin resin (A) and the polypropylene resin (E) is equal to or less than the upper limit, sufficient releasability is ensured.
[0085] The total mass ratio of the modified polyolefin resin (A) and the polypropylene resin (E) may be, for example, 10 mass% or more and 98 mass% or less, 20 mass% or more and 97 mass% or less, 30 mass% or more and 96 mass% or less, or 40 mass% or more and 95 mass% or less.
[0086] When the resin composition contains a polyethylene-based resin (D) and a polypropylene-based resin (E), the proportion of the total mass of the modified polyolefin-based resin (A), the polyethylene-based resin (D) and the polypropylene-based resin (E) relative to the total mass of the resin composition is preferably 30 mass% or more, more preferably 35 mass% or more, even more preferably 40 mass% or more, still more preferably 45 mass% or more, while being preferably 99 mass% or less, more preferably 98 mass% or less, even more preferably 97 mass% or less, still more preferably 96 mass% or less, and particularly preferably 95 mass% or less. When the total mass ratio of the modified polyolefin resin (A), the polyethylene resin (D) and the polypropylene resin (E) is equal to or greater than the lower limit, the adhesiveness to a resin battery case or a metal plate and the film formability can be achieved. When the total mass ratio of the modified polyolefin resin (A), the polyethylene resin (D) and the polypropylene resin (E) is equal to or less than the upper limit, sufficient peelability is ensured.
[0087] The total mass ratio of the modified polyolefin-based resin (A), the polyethylene-based resin (D) and the polypropylene-based resin (E) may be, for example, 30% by mass or more and 99% by mass or less, 35% by mass or more and 98% by mass or less, 40% by mass or more and 97% by mass or less, 45% by mass or more and 96% by mass or less, or 45% by mass or more and 95% by mass or less.
[0088] The ratio of the total mass of the modified polyolefin resin (A), the thermally expandable flame retardant (Ba) or the thermally expandable foaming agent (Bb), the copolymer (C), and the polyethylene resin (D) and / or the polypropylene resin (E) that may be contained as necessary to the total mass of the present resin composition is preferably 60 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, particularly preferably 90 mass% or more, and may be 100 mass%. For example, when the total mass of the component (A), the component (B) (meaning the above-mentioned thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb)), the component (C), the contained component (D) and / or the component (E) is 100 mass%, the modified polyolefin resin (A), the thermally expandable flame retardant (Ba) or the thermally expandable foaming agent (Bb), the copolymer (C), the polyethylene resin (D) and / or the polypropylene resin (E) can be appropriately selected within the above-mentioned amount range so that the total of the four or five components is 100 mass%.
[0089] <Other flame retardants or flame retardant auxiliaries> As the other flame retardant or flame retardant assistant, a conventionally known phosphorus-based flame retardant, a bromine-based flame retardant, an antimony-based flame retardant, etc. other than the thermally expandable flame retardant (Ba), or an organic or inorganic flame retardant or flame retardant assistant not containing a halogen is preferable. As such a flame retardant or flame retardant assistant, for example, at least one selected from the group consisting of a triazine ring-containing compound, a silicone-based flame retardant, a metal hydroxide, a metal oxide, a boric acid compound, and an expandable graphite can be mentioned.
[0090] Examples of the triazine ring-containing compound include melamine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, and 1,3-hexylenedimelamine. Examples of silicone-based flame retardants include silicone oil, silicone rubber, and silicone resin. Examples of metal hydroxides include magnesium hydroxide, aluminum hydroxide, calcium hydroxide, barium hydroxide, zinc hydroxide, Kismer 5A (a trademark of magnesium hydroxide manufactured by Kyowa Chemical Industry Co., Ltd.), and the like. Examples of metal oxides include inorganic compounds such as zinc oxide, titanium oxide, aluminum oxide, magnesium oxide, titanium dioxide, and hydrotalcite, and surface-treated products thereof. Specific examples of metal oxides include TIPAQUE R-680 (trademark of titanium oxide manufactured by Ishihara Sangyo Kaisha), Kyowamag 150 (trademark of magnesium oxide manufactured by Kyowa Chemical Industry Co., Ltd.), DHT-4A (hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.), and Alcamizer 4 (trademark of zinc-modified hydrotalcite manufactured by Kyowa Chemical Industry Co., Ltd.). An example of the boric acid compound is zinc borate. These flame retardants or flame retardant auxiliaries may be used alone or in combination of two or more kinds.
[0091] <Foaming agent> The resin composition may contain a foaming agent (excluding the foaming agent (Bb)) in addition to the modified polyolefin resin (A), the thermally expandable flame retardant (Ba), the thermally expandable foaming agent (Bb), and the copolymer (C) of α-olefin and unsaturated carboxylic acid. By containing a foaming agent, in addition to the expansion layer being formed by the thermally expandable flame retardant (Ba) or the thermally expandable foaming agent (Bb) during combustion, a foam layer can be formed by the foaming agent. For example, when the foaming temperature of the foaming agent is lower than the expansion temperature of the thermally expandable flame retardant (Ba) or the thermally expandable foaming agent (Bb), a foam layer is formed by the foaming agent first, and then an expansion layer by the thermally expandable flame retardant (Ba) or the thermally expandable foaming agent (Bb) can be formed, so that dismantling property during recycling and heat insulation property during thermal runaway can be more effectively expressed.
[0092] The foaming agent is not particularly limited as long as it foams when heated and exhibits a heat insulating effect by interacting with the non-halogen phosphate compound. Specific examples of the foaming agent include water; low-boiling point hydrocarbons such as propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane; chlorinated aliphatic hydrocarbon compounds such as dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride; fluorine compounds such as trichloromonofluoromethane and trichlorotrifluoroethane; CHF 3 , C.H. 2 F 2 , C.H. 3 Hydrofluorocarbons such as F; hydrochlorofluorocarbon compounds such as dichloromonofluoroethane (e.g., HCFC141b (1,1-dichloro-1-fluoroethane)), HCFC22 (chlorodifluoromethane), HCFC142b (1-chloro-1,1-difluoroethane), HFC-245fa (1,1,1,3,3-pentafluoropropane), and HFC-365mfc (1,1,1,3,3-pentafluorobutane); HFO-1233zd (trans-1-chloro-3,3,3-trifluoropropene) Examples of the physical blowing agents include hydrofluoroolefin compounds such as HFO-1234yf (2,3,3,3-tetrafluoro-1-propene), HFO-1234ze (trans-1,3,3,3-tetrafluoropropene); organic physical blowing agents such as ether compounds such as diisopropyl ether, or mixtures of these compounds; and inorganic physical blowing agents such as nitrogen gas, oxygen gas, argon gas, carbon dioxide gas, or subcritical fluids and / or supercritical fluids thereof (the above gases and their subcritical fluids / supercritical fluids may be mixed gases). Of these, water and an organic physical blowing agent are preferred, and water and a hydrofluoroolefin compound are more preferred.
[0093] The content of the foaming agent is preferably in the range of 0.1 parts by mass or more and 40 parts by mass or less, and more preferably in the range of 0.1 parts by mass or more and 35 parts by mass or less, per 100 parts by mass of the total mass of the modified polyolefin-based resin (A) and the polyethylene-based resin (D) and / or polypropylene-based resin (E) that may be contained as necessary. When the content of the foaming agent is 0.1 parts by mass or more, foaming is promoted, and when the content is 40 parts by mass or less, a foam is formed.
[0094] <Other ingredients> The resin composition may contain other components within the range not impairing the effects of the present invention, such as at least one selected from the group consisting of inorganic fiber fillers, interfacial strength improvers, antioxidants, ultraviolet absorbers, light stabilizers, and antiaging agents. For example, the inorganic fiber filler may contain at least one type of inorganic fiber filler selected from the group consisting of glass fiber and carbon fiber, and one type of inorganic fiber filler may be used alone or two or more types may be used in combination. As the interfacial strength improver, a polymer having an olefin skeleton (excluding the modified polyolefin resin (A) and the copolymer (C)) is preferable, particularly from the viewpoint of compatibility with the modified polyolefin resin. The interfacial strength is further improved by the compatibility of the olefin skeleton with the modified polyolefin resin. Examples of commercially available interfacial strength improvers include UMEX 1001 and 1010 (manufactured by Sanyo Chemical Industries, Ltd.), and Kayabrid 002PP and 003PP (manufactured by Nouryon Chemical Co., Ltd.).
[0095] Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, and thioether-based antioxidants. Examples of ultraviolet absorbers include 2-hydroxybenzophenones, 2-(2'-hydroxyphenyl)benzotriazoles, benzoates, substituted oxanilides, cyanoacrylates, and triaryltriazines. As the light stabilizer, a hindered amine compound can be used.
[0096] In addition to the above, the present resin composition may contain a plasticizer, a fluorine-containing drip-preventing agent, and commonly used additives such as a crosslinking agent, an antistatic agent, a metal soap, a filling agent, an antifogging agent, an antiplate-out agent, a surface treatment agent, a fluorescent agent, an antifungal agent, a bactericide, a foaming agent, a metal deactivator, a release agent, a pigment, and a processing aid, within a range that does not impair the effects of the present invention.
[0097] [Method of producing resin composition] Any method can be used to produce the resin composition. For example, the modified polyolefin resin (A), the heat expandable flame retardant (Ba), the heat expandable foaming agent (Bb), the copolymer (C), and optionally the polyethylene resin (D), the polypropylene resin (E), other flame retardants, flame retardant auxiliaries, and other components are thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, or an extrusion mixer, and optionally granulated using an extrusion granulator or a briquetting machine, and then melt-kneaded and extruded using a melt mixer. The process for obtaining the resin composition may be a one-step process in which all of the raw materials are fed into an extruder at once and melt-kneaded, or a two-step process in which only some of the raw materials, for example only the resin components, more specifically the modified polyolefin-based resin (A), the polyethylene-based resin (D) and the polypropylene-based resin (E), are pre-kneaded to prepare a mixture, and then the mixture is used as a raw material to melt-knead with the thermally expandable flame retardant (Ba), the thermally expandable foaming agent (Bb) and the copolymer (C).
[0098] Examples of the melt kneader include a twin-screw extruder such as a vented twin-screw extruder, a Banbury mixer, a kneading roll, a single-screw extruder, and a multi-screw extruder having three or more screws. The temperature during melt kneading is, for example, 170° C. or higher and 260° C. or lower. The resin composition extruded as described above is directly cut into pellets by a machine such as a pelletizer, or is cooled to form strands, and then the strands are cut into pellets by a machine such as a pelletizer.
[0099] As described in detail above, the resin composition contains the copolymer (C) in addition to the modified polyolefin resin (A), the thermally expandable flame retardant (Ba), and the thermally expandable foaming agent (Bb), and therefore can fully maintain the inherent physical properties (e.g., high mechanical strength and adhesiveness) of the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary. The copolymer (C) improves the dispersibility of the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) in the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary. It is believed that the improved dispersibility of the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) makes it easier for a heat insulating layer (expansion layer) to be formed during combustion, improving dismantling properties and heat insulation. The mechanism behind this is unclear, but the following is thought to be the cause.
[0100] The modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as required are classified as low-polarity resins among thermoplastic resins, and it is difficult to disperse polar additives such as the thermally expandable flame retardant (Ba) containing the above-mentioned phosphorus-based compound and the thermally expandable blowing agent (Bb). On the other hand, the copolymer (C) has a low-polarity α-olefin moiety that is excellent in compatibility with the modified polyolefin resin (A) and the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as required, and a polar unsaturated carboxylic acid moiety that is excellent in compatibility with the thermally expandable flame retardant (Ba) and the thermally expandable blowing agent (Bb). When the resin composition is melt-kneaded, the presence of copolymer (C) between the modified polyolefin resin (A) or the polyethylene resin (D) and / or polypropylene resin (E) which may be contained as necessary and the thermally expandable flame retardant (Ba) or the thermally expandable blowing agent (Bb) is considered to improve the dispersibility of the thermally expandable flame retardant (Ba) or the thermally expandable blowing agent (Bb) in the modified polyolefin resin (A) or the polyethylene resin (D) and / or polypropylene resin (E) which may be contained as necessary.
[0101] The effects of the copolymer (C) include (1) improving the dispersibility of the thermally expandable flame retardant (Ba) and the thermally expandable foaming agent (Bb) (finely dispersing), (2) promoting the formation of an insulating layer (expansion layer) during combustion, and (3) improving physical properties (tensile strain at break).
[0102] Specifically, when the resin composition contains the thermally expandable flame retardant (Ba), the effect of burning the resin composition is as follows: when a flat plate test piece obtained by molding a resin composition containing the modified polyolefin resin (A), the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary, and the thermally expandable flame retardant (Ba) is burned with a burner, if the resin composition does not contain the copolymer (C), small and many chars are formed on the surface, but if the resin composition contains the copolymer (C), the size of the char increases, and the heat transfer suppression effect is improved. In addition, in a cone calorimeter test, when a 3 mm thick flat plate obtained by molding a resin composition containing the modified polyolefin resin (A), the polyethylene resin (D) and / or polypropylene resin (E) that may be contained as necessary, and the thermally expandable flame retardant (Ba) is burned by radiant heat, if the resin composition does not contain the copolymer (C), many gaps in the char are generated and the molded body burns, but if the resin composition contains the copolymer (C), the gaps in the char are reduced, and char is formed by burning on the side, forming a dome shape. Although the mechanism is unclear, the addition of copolymer (C) forms a stronger char (expansion layer), suppressing heat transfer and achieving high flame retardancy. For example, it is possible to achieve V-0 in the UL94 test. The copolymer (C) can exert the above effects even in a small amount.
[0103] [Molded body] The molded article according to one embodiment of the present invention is obtained by molding the above-mentioned resin composition. An example of the molded article is an adhesive sheet molded into a sheet shape.
[0104] For example, in a battery pack 1 as shown in FIG. 1, a sheet formed from the present resin composition can be used as an adhesive sheet 14. The adhesive sheet 14 formed from the present resin composition realizes high adhesion between a resin battery casing 15 and a metal plate (cooling plate) 13 when the battery is in use, and can be easily disassembled during disassembly for recycling or the like. That is, at the stage of use as a battery, sufficient cooling is performed so that the battery casing 15 and the metal plate (cooling plate) 13 are firmly adhered to each other. On the other hand, when the battery is to be disposed of, the adhesive sheet 14 is expanded by heating, the adhesive force between the metal plate (cooling plate) 13 and the battery casing 15 is reduced, and the metal plate (cooling plate) 13 can be easily peeled off from the battery casing 15, so that they can be separated from each other and recycled easily.
[0105] For example, in a battery pack 2 as shown in FIG. 2, a sheet formed from the present resin composition can be used as an adhesive sheet 23. The adhesive sheet 23 formed from the present resin composition is used as an adhesive sheet 23 that transfers heat from the battery cell 21 to a metal plate (cooling plate) 24 and is attached to the battery cell 21, and while it achieves good thermal conductivity at all times, it can also contribute to blocking heat during thermal runaway. That is, at the stage of use as a battery, the battery cell 21 and the metal plate (cooling plate) 24 are firmly bonded to each other, so that the adhesive sheet 23 has excellent thermal conductivity. On the other hand, during thermal runaway, when the battery cell becomes abnormally hot, the adhesive sheet 23 expands due to heating and forms a heat insulating layer, blocking heat from the battery cell 21 and suppressing heat transfer to other battery cells 21, or the adhesive force between the battery cell 21 and the metal plate (cooling plate) 24 is reduced, so that the heat blocking property is improved.
[0106] The thickness of the adhesive sheet is preferably in the range of 0.05 mm to 2 mm. If the thickness of the adhesive sheet is 0.05 mm or more, the adhesive strength and heat insulation are sufficient, and if the thickness is 2 mm or less, peeling during disassembly is easy and good thermal conductivity can be achieved. From the above viewpoints, the thickness of the adhesive sheet is more preferably in the range of 0.1 mm to 1 mm.
[0107] An example in which the sheet-shaped adhesive sheet, which is the molded article of the present invention, is used in a battery pack will be described below. The battery pack has, for example, the configuration shown in Figures 1 and 2, and the method of using the adhesive sheet is as described above. That is, the battery pack has a battery cell, a spacer, a metal plate (cooling plate), an adhesive sheet, and a battery housing, and in the example shown in Figure 1, the adhesive sheet bonds the metal plate (cooling plate) and the battery housing, and in the example shown in Figure 2, the adhesive sheet bonds the battery cell and the metal plate (cooling plate).
[0108] The components that make up the battery pack will be described below. (Battery Cell) The battery cell in the battery pack is not particularly limited, but is usually configured by housing a positive electrode, a negative electrode, a separator, and an electrolyte solution in the battery cell. Examples of the material of the battery cell include metals such as iron, aluminum, and aluminum alloys; laminate films, etc. From the viewpoints of weight reduction and cost, the material of the battery cell is preferably metal or laminate film, and from the viewpoint of pressure resistance, more preferably iron.
[0109] The positive electrode contains a positive electrode active material on at least a portion of the surface of a current collector. There are no particular limitations on the positive electrode active material as long as it is capable of electrochemically absorbing and releasing metal ions.
[0110] Examples of the positive electrode active material include lithium transition metal compounds, sodium transition metal compounds, and potassium transition metal compounds. The positive electrode active material may be used alone or in any ratio and combination of two or more. From the viewpoint of increasing the energy density of the battery, the positive electrode active material is preferably a lithium transition metal compound, a sodium transition metal compound, or a potassium transition metal compound, more preferably a lithium transition metal compound, and further preferably a lithium transition metal composite oxide. Examples of the structure of the lithium transition metal composite oxide include a spinel structure, an olivine structure, a layered structure, etc. From the viewpoints of battery capacity and durability, the structure of the lithium transition metal composite oxide is preferably a spinel structure, an olivine structure, or a layered structure, and from the viewpoint of increasing the battery capacity, a layered structure is more preferable.
[0111] Examples of the material for the positive electrode current collector include metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc. From the viewpoint of increasing the energy density of the battery, the material for the positive electrode current collector is preferably aluminum.
[0112] The negative electrode contains a negative electrode active material on at least a portion of the surface of a current collector. There are no particular limitations on the negative electrode active material as long as it is capable of electrochemically absorbing and releasing metal ions.
[0113] Examples of the negative electrode active material include carbonaceous materials and metal materials. The negative electrode active material may be used alone or in any ratio and combination of two or more. From the viewpoint of cycle characteristics and continuous charging characteristics, the negative electrode active material is preferably a carbonaceous material, a metal material, or a mixture of a carbonaceous material and a metal material. Examples of carbonaceous materials that can be used as negative electrode active materials include natural graphite such as uncoated natural graphite, amorphous carbon-coated natural graphite, graphite-coated natural graphite, and resin-coated natural graphite; artificial graphite; and amorphous carbon. The carbonaceous materials may be used alone or in any combination of two or more kinds in any ratio. The carbonaceous material is preferably natural graphite from the viewpoint of increasing the battery capacity. Examples of natural graphite include scaly natural graphite, scaly natural graphite, and natural graphite obtained by subjecting such graphite to treatment such as spheroidization or densification. One type of natural graphite may be used alone, or two or more types may be used in any ratio and combination. From the viewpoints of packing property and charge / discharge rate characteristics, spheroidized natural graphite is preferred. The metal material that becomes the negative electrode active material is a material that contains a metal element and / or a metalloid element that can be alloyed with an alkali metal, and from the viewpoint of increasing capacity, an oxide of silicon, silicon oxide, or silicon carbide is preferable.
[0114] Examples of the material for the negative electrode current collector include metal materials such as aluminum, copper, nickel, stainless steel, nickel-plated steel, etc. Copper is preferred as the material for the negative electrode current collector because it does not alloy with alkali metals and is inexpensive.
[0115] The material of the separator is preferably polyethylene, polypropylene, cellulose, or polyvinylidene fluoride, and more preferably polyethylene or polypropylene. The separator is preferably in the form of a porous film or a nonwoven fabric, and more preferably in the form of a porous film.
[0116] The electrolytic solution usually contains an electrolyte and a non-aqueous solvent. The electrolyte is preferably an alkali metal salt from the viewpoint of increasing solubility, more preferably a lithium salt, a sodium salt, or a potassium salt, and even more preferably a lithium salt from the viewpoint of improving cycle characteristics. Examples of the lithium salt include lithium fluoroborate salt, lithium fluorophosphate salt, lithium tungstate salt, lithium carboxylate salt, lithium sulfonate salt, lithium imide salt, lithium methide salt, lithium oxalate salt, and fluorine-containing organic lithium salt. The lithium salt may be used alone or in any ratio and combination of two or more kinds. The lithium salt is preferably LiBF from the viewpoint of improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, and cycle characteristics. 4 , LiPF 6 , Li 2 PO3 F, LiPO 2 F 2 , LiFSO 3 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, C.H. 3 SO 4 Li, C.F. 3 SO 4 Li, C. 2 H 5 SO 4 Li, C. 2 F 5 SO 4 Li, C. 3 H 5 SO 4 Li, C. 3 H 3 SO 4 Li, LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 , lithium difluorooxalatoborate, lithium bis(oxalato)borate, lithium tetrafluorooxalatophosphate, lithium difluorobis(oxalato)phosphate, and lithium tris(oxalato)phosphate are preferred, and from the viewpoint of improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, and cycle characteristics, LiBF 4 , LiPF 6 , LiPO2 F 2 , LiN(FSO 2 ) 2 , lithium bis(oxalato)borate, LiFSO 3 is more preferable, and from the viewpoint of further improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, and cycle characteristics, LiPF 6 is more preferred.
[0117] The non-aqueous solvent is preferably an organic solvent from the viewpoint of suppressing oxidation-reduction decomposition in the battery. Examples of the organic solvent include saturated cyclic carbonates, chain carbonates, chain carboxylates, cyclic carboxylates, ether compounds, and sulfone compounds. The organic solvent may be used alone or in any ratio and combination of two or more. From the viewpoint of suppressing oxidation-reduction decomposition in the battery, the organic solvent is preferably a saturated cyclic carbonate, chain carbonate, chain carboxylate, cyclic carboxylate, ether compound, or sulfone compound, and more preferably a saturated cyclic carbonate, chain carbonate, or chain carboxylate.
[0118] The electrolytic solution may contain other compounds in addition to the electrolyte and the non-aqueous solvent. Examples of the other compounds include unsaturated cyclic carbonates, fluorine-containing cyclic carbonates, isocyanate group-containing organic compounds, isocyanuric acid skeleton-containing organic compounds, sulfur-containing organic compounds, phosphorus-containing organic compounds, silicon-containing compounds, aromatic compounds, cyano group-containing organic compounds, acid anhydride compounds, and triple bond-containing compounds. The other compounds may be used alone or in any ratio and combination of two or more. From the viewpoint of improving low-temperature output characteristics, high-rate charge / discharge characteristics, impedance characteristics, high-temperature storage characteristics, and cycle characteristics, the other compounds are preferably unsaturated cyclic carbonates, fluorine-containing cyclic carbonates, isocyanate group-containing organic compounds, isocyanuric acid skeleton-containing organic compounds, sulfur-containing organic compounds, phosphorus-containing organic compounds, silicon-containing compounds, aromatic compounds, cyano group-containing organic compounds, acid anhydride compounds, and triple bond-containing compounds, more preferably unsaturated cyclic carbonates, fluorine-containing cyclic carbonates, isocyanate group-containing organic compounds, and isocyanuric acid skeleton-containing organic compounds, and even more preferably unsaturated cyclic carbonates and fluorine-containing cyclic carbonates.
[0119] (metal plate) The metal plate in the battery pack is not particularly limited as long as it is a metal that is generally used as a cooling plate for a battery, and metals with high thermal conductivity such as SUS, aluminum, and copper are preferably used. The thickness of the metal plate is preferably in the range of 0.5 mm to 5 mm, more preferably in the range of 1 mm to 3 mm. If the thickness is equal to or greater than the lower limit, heat conduction is sufficient, and the cooling effect of the battery cell is sufficient. On the other hand, if the thickness is equal to or less than the upper limit, it is preferable from the viewpoint of reducing the weight of the battery.
[0120] (Battery housing) The battery casing in the battery pack is not particularly limited, but the resin battery casing (hereinafter, sometimes referred to as a resin casing) is not particularly limited, and at least one of a thermosetting resin and a thermoplastic resin can be used. Among these, a thermoplastic resin is particularly preferred. That is, the resin casing is preferably made of a molded body containing a thermoplastic resin. Examples of the thermoplastic resin include polyolefin resin, polycarbonate resin, polyester resin, acrylonitrile styrene resin, ABS resin, polyamide resin, modified polyphenylene oxide, etc. Among them, polyolefin resin, polyester resin, and polyamide resin are preferred, and at least one selected from polypropylene, polyethylene terephthalate, and nylon is particularly preferred, and polypropylene is more preferred.
[0121] The thickness of the resin housing is not particularly limited, but is, for example, not less than 5 μm and not more than 200 μm. Furthermore, the resin housing has two exterior bodies whose peripheral portions are joined into a ring shape by heat fusion, adhesion, etc., so that the liquid and the heat insulating material are hermetically sealed within the housing. Alternatively, one resin housing may be folded and its peripheral portions joined by heat fusion, adhesion, etc., so that the liquid and the heat insulating material are hermetically sealed within the housing. It is preferable that the resin housing has flexibility (elasticity), but there may be cases where it does not have flexibility. It is preferable that the internal pressure of the resin housing is lower than the external pressure in order to sufficiently increase the opening temperature, and therefore it is particularly preferable to vacuum seal the resin housing. EXAMPLES
[0122] The present invention will be described in detail below using examples, but the present invention is not limited to these examples. In particular, the process for obtaining the resin composition of the present invention may be a one-step process in which all raw materials are put into an extruder at once and melt-kneaded, or a two-step process in which only some raw materials, for example, resin components (component (A), component (D), and component (E)) are pre-kneaded to prepare a mixture, and the mixture is used as a raw material to melt-knead with component (B) and component (C).
[0123] (Evaluation method) 1.Thermal diffusivity reduction rate The thermal diffusivity was measured before and after heating by the following method, and the rate of decrease in thermal diffusivity before and after heating was calculated. (Thermal diffusivity) For the thermal diffusivity test piece described later, the thermal diffusivity was measured in the thickness direction of the thermal diffusivity test piece at a measurement temperature of 25°C by the laser flash method using a Xe flash analyzer LFA447 Nanoflash manufactured by Netsch Japan Co., Ltd., and the thermal diffusivity was recorded as the thermal diffusivity before heating. 2 As there are no JIS standards for the thermal diffusivity and thermal conductivity of resin-based materials, JIS R1611:2010 (Method of measurement of thermal diffusivity, specific heat capacity, and thermal conductivity of fine ceramics by the flash method) was used as reference, and as this standard specifies that "the sample thickness shall be 0.5 mm or more and 5 mm or less," the thickness of the test piece was set to 1.0 mm, as described below. Next, the thermal diffusivity test piece was heated at 285° C. for 5 minutes and then held at room temperature (25° C.) overnight, after which the thermal diffusivity was measured in the same manner as above and recorded as the thermal diffusivity after heating. (Reduction rate of thermal diffusivity) The rate of decrease in thermal diffusivity was calculated based on the following formula (1). Reduction rate of thermal diffusivity (%) = ((thermal diffusivity before heating – thermal diffusivity after heating) / thermal diffusivity before heating) × 100 (1)
[0124] 2. Adhesive force reduction rate The adhesive strength was measured before and after heating by the following method, and the reduction rate of the adhesive strength before and after heating was calculated. (adhesive strength) The adhesive strength test piece described below was sandwiched between an aluminum plate (standard test plate A5052P, Japan Test Panel Co., Ltd.) of length 100 mm x width 25 mm x thickness 1.6 mm, and press-bonded at 160°C. The peel strength of the adhesive strength test piece and the aluminum plate was measured using an Inteslon 200X universal testing machine in accordance with JIS K6850-1999 <Test method for tensile shear adhesive strength between adhesive and rigid adherend>. Measurements were performed three times for each sample, and the average value was taken as the adhesive strength before heating. Next, the adhesive strength test piece sandwiched between the aluminum plates was heated at 285°C for 5 minutes, and then held at room temperature (25°C) overnight, after which the peel strength was measured in the same manner as above. The measurement after heating was also performed three times for each sample, and the average value was taken as the adhesive strength after heating. (Decrease rate of adhesive force) The rate of decrease in adhesive strength was calculated based on the following formula (2). Decrease rate of adhesive strength (%) = ((adhesive strength before heating - adhesive strength after heating) / adhesive strength before heating) × 100 (2)
[0125] 3.Expansion evaluation The thermal diffusivity test piece described below was heated at 285°C for 5 minutes and then held at room temperature (25°C) overnight, after which the length, width and thickness of the thermal diffusivity test piece were measured and the volume was calculated. Note that the test piece containing a thermally expandable material formed a fine expansion layer / foam layer by heating at 285°C for 5 minutes, and it is believed that the higher the expansibility of the test piece, the greater the proportion of the expansion layer / foam layer, which is believed to result in a higher heat transfer inhibition effect. ◎ (Excellent): The sample volume after heating was 2.0 times or more the volume before heating. 〇 (good): The sample volume after heating was more than 1.5 times and less than 2.0 times the sample volume before heating. × (poor): The sample volume after heating was 1.5 times or less the sample volume before heating.
[0126] 4. Peelability evaluation An adhesion test piece described later was sandwiched between an aluminum plate of length 100 mm x width 25 mm x thickness 1.6 mm (standard test plate A5052P, manufactured by Nippon Test Panel Co., Ltd.) and a glass mat reinforced thermoplastic (GMT) plate of length 100 mm x width 25 mm x thickness 2.5 mm ("GMT eFR", manufactured by Mitsubishi Chemical Advanced Materials Corporation), and the aluminum plate side was set to 160°C with a hot plate set to 120°C with the GMT plate side, and the test pieces were press-bonded. Next, the adhesion test piece sandwiched between the aluminum plate and the GMT plate was heated at 285° C. for 5 minutes and then held at room temperature (25° C.) overnight, after which the peelability was evaluated according to the following. 〇 (good): The aluminum plate and the GMT plate could be easily peeled off by hand from the heated sample. × (poor): The aluminum plate and the GMT plate could not be easily peeled off by hand from the heated sample.
[0127] (Resin composition raw material) (A-1) Modified polyolefin resin Modified polyolefin resin consisting of a binary copolymer in which maleic acid is graft-polymerized onto polyolefin resin ("Modic X2036H" manufactured by Mitsubishi Chemical Corporation, MFR (180°C, load 2.16 kg, 1 mm diameter orifice): 0.5 g / 10 min, melting point: 125°C) (A-2) Modified polyolefin resin A modified propylene polymer obtained by graft-modifying a commercially available propylene homopolymer [MFR (230°C, load 2.16 kg, 2 mm diameter orifice): 10.0 g / 10 min, melting point: 162°C] with maleic anhydride [modification rate (graft rate): 2.5 mass%, MFR (180°C, load 2.16 kg, 1 mm diameter orifice): 300 g / 10 min, melting point: 158°C] (A-3) Modified polyolefin resin A modified propylene polymer obtained by graft-modifying 56% by mass of a commercially available propylene-ethylene random copolymer [MFR (230°C, load 2.16 kg, 2 mm diameter orifice): 7 g / 10 min, melting point: 135°C] and 44% by mass of a commercially available propylene-ethylene random copolymer [MFR (230°C, load 2.16 kg, 2 mm diameter orifice): 8 g / 10 min, melting point: 59°C] with maleic anhydride [modification rate (graft rate): 0.9% by mass, MFR (180°C, load 2.16 kg, 1 mm diameter orifice): 8 g / 10 min, melting point: 132°C] (A-4) Modified polyolefin resin A modified propylene polymer obtained by graft-modifying 60% by mass of a commercially available propylene-ethylene random copolymer [MFR (230°C, load 2.16 kg, 2 mm diameter orifice): 30 g / 10 min, melting point: 143°C], 20% by mass of a commercially available propylene-ethylene random copolymer [MFR (230°C, load 2.16 kg, 2 mm diameter orifice): 7 g / 10 min, melting point: 135°C], and 20% by mass of a commercially available propylene-ethylene random copolymer [MFR (230°C, load 2.16 kg, 2 mm diameter orifice): 3 g / 10 min, melting point: 95°C] with maleic anhydride [modification rate (graft rate): 0.9 mass%, MFR (180°C, load 2.16 kg, 1 mm diameter orifice): 11 g / 10 min, melting point: 136°C]
[0128] (Ba) Thermally expandable flame retardant Phosphorus-based flame retardant (ADEKA CORPORATION, Adeka STAB FP-2500S, an intumescent flame retardant containing 50-60 mass% piperazine pyrophosphate, 35-45 mass% melamine pyrophosphate, and 3-6 mass% zinc oxide relative to the total mass of the phosphorus-based flame retardant composition) (Bb) Thermally expandable foaming agent Thermally expandable microcapsules containing a foaming component (hydrocarbon) inside an acrylic resin (in the examples, Kureha Microsphere MB-S6LC manufactured by Kureha Corporation was used. However, MB-S6LC is a master batch of the thermally expandable foaming agent and low-density polyethylene (LDPE: (D-2) polyethylene resin), and MB-S6LC contains 50% by mass of the thermally expandable foaming agent relative to its total mass.)
[0129] (C) Copolymer α-Olefin-maleic anhydride copolymer (Mitsubishi Chemical Corporation, Diacalna 30M, weight average molecular weight 7,800)
[0130] (D-1) Polyethylene resin Low-density polyethylene [MFR (190°C, load 2.16 kg, 2 mm orifice): 4 g / 10 min, melting point: 107°C] (D-2) Polyethylene resin Low Density Polyethylene (LDPE)
[0131] (E-1) Polypropylene resin Propylene homopolymer [MFR (230°C, load 21.2N, orifice 2mm diameter): 11.0g / 10min, melting point: 170°C] (E-2) Polypropylene resin Propylene-ethylene random copolymer [MFR (230°C, load 21.2N, orifice 2mm diameter): 20g / 10min, melting point: 145°C] (E-3): Polypropylene resin Propylene-ethylene random copolymer [MFR (230°C, load 21.2N, orifice 2mm diameter): 2g / 10min, melting point: 125°C] (E-4): Polypropylene resin Propylene-ethylene random copolymer [MFR (230°C, load 21.2N, orifice 2mm diameter): 3g / 10min, melting point: 95°C]
[0132] Example 1 The (A-1) modified polyolefin resin, (Ba) thermally expandable flame retardant, and (C) copolymer were mixed by hand blending so that the ratio of each raw material was as shown in Table 1 below. Then, using a φ30 mm co-rotating twin screw extruder (model name "BT-30", manufactured by Plastics Engineering Research Institute Co., Ltd., L / D=30), the mixture was melt-kneaded at a screw rotation speed of 250 rpm and a cylinder temperature of 200°C to obtain a pellet-shaped resin composition (hereinafter sometimes referred to as the present pellets). Here, "L / D" indicates the ratio of the screw length (L) to the diameter (D). The pellets were then used to prepare the following molded articles (adhesive sheets) and the evaluations were carried out. The evaluation results are shown in Table 1.
[0133] The obtained pellets were press molded using a 40t high-performance high-temperature vacuum press (model name "VH1-1747", manufactured by Kitagawa Seiki Co., Ltd.) under conditions of a molding temperature of 200°C and a molding pressure of 3.0 MPa to obtain an adhesive sheet (length 200 mm x width 150 mm x thickness 1.0 mm). A 10 mm length x 10 mm width specimen was cut from this adhesive sheet to prepare a test piece for thermal diffusivity. The obtained pellets were press molded using a 40t high-performance high-temperature vacuum press (model name "VH1-1747", Kitagawa Seiki Co., Ltd.) under conditions of a molding temperature of 200°C and a molding pressure of 3.0 MPa to obtain an adhesive sheet (length 200 mm x width 150 mm x thickness 1.6 mm). A strip of length 12.5 mm x width 25 mm was cut from this adhesive sheet to prepare a test piece for adhesion.
[0134] Example 2 (A-2) modified polyolefin resin 8 mass%, (D-1) polyethylene resin 5 mass%, (E-1) polypropylene resin 5 mass%, (E-2) polypropylene resin 82 mass% were mixed in advance by dry blending, and melt-kneaded using a twin-screw extruder TEX25 (manufactured by JSW Corporation) at a temperature of 200°C, a screw rotation speed of 300 rpm, and an extrusion rate of 20 kg / h. The mixture was extruded into a strand, cooled, and then cut to obtain a pellet-like mixture. Thereafter, a molded article (adhesive sheet) was produced and each evaluation was carried out in the same manner as in Example 1, except that the mixture was used instead of (A-1) in Example 1. The final composition of the resin composition and the evaluation results are shown in Table 1.
[0135] Example 3 A molded article (adhesive sheet) was produced and evaluated in the same manner as in Example 1, except that 89.5% by mass of (A-1) modified polyolefin resin, 10% by mass of MB-S6LC (i.e., 5% by mass of (Bb) thermally expandable foaming agent and 5% by mass of (D-2) polyethylene resin LDPE), and 0.5% by mass of (C) copolymer were used. The composition of the final resin composition and the evaluation results are shown in Table 1.
[0136] Example 4 (A-2) modified polyolefin resin 8 mass%, (D-1) polyethylene resin 5 mass%, (E-1) polypropylene resin 5 mass%, (E-2) polypropylene resin 82 mass% were mixed in advance by dry blending, and melt-kneaded using a twin-screw extruder TEX25 (manufactured by JSW Corporation) at a temperature of 200°C, a screw rotation speed of 300 rpm, and an extrusion rate of 20 kg / h. The mixture was extruded into a strand, cooled, and then cut to obtain a pellet-like mixture. Thereafter, a molded product (adhesive sheet) was produced and each evaluation was performed in the same manner as in Example 3, except that the mixture was used instead of (A-1) in Example 3. The final composition of the easily dismantlable adhesive material and its evaluation results are shown in Table 1.
[0137] Example 5 (A-2) 3% by mass of modified polyolefin resin, (A-3) 15% by mass of modified polyolefin resin, (D-1) 10% by mass of polyethylene resin, (E-3) 20% by mass of polypropylene resin, and (E-4) 52% by mass of polypropylene resin were mixed in advance by dry blending, and melt-kneaded using a twin-screw extruder TEX25 (manufactured by JSW Corporation) at a temperature of 200°C, a screw rotation speed of 300 rpm, and an extrusion rate of 20 kg / h. The mixture was extruded into a strand, cooled, and then cut to obtain a pellet-like mixture. Thereafter, a molded product (adhesive sheet) was produced and each evaluation was performed in the same manner as in Example 3, except that the mixture was used instead of (A-1) in Example 3. The final composition of the easily dismantlable adhesive material and its evaluation results are shown in Table 1.
[0138] Example 6 (A-4) modified polyolefin resin 30 mass%, (D-1) polyethylene resin 10 mass%, (E-3) polypropylene resin 15 mass%, and (E-4) polypropylene resin 45 mass% were mixed in advance by dry blending, and melt-kneaded using a twin-screw extruder TEX25 (manufactured by JSW Corporation) at a temperature of 200°C, a screw rotation speed of 300 rpm, and an extrusion rate of 20 kg / h. The mixture was extruded into a strand, cooled, and then cut to obtain a pellet-like mixture. Thereafter, a molded product (adhesive sheet) was produced and each evaluation was performed in the same manner as in Example 3, except that the mixture was used instead of (A-1) in Example 3. The final composition of the easily dismantlable adhesive material and its evaluation results are shown in Table 1.
[0139] Comparative Example 1 A molded article (adhesive sheet) was produced using 100% by mass of the modified polyolefin resin (A-1), and various evaluations were performed. The final composition of the easily dismantled adhesive material and its evaluation results are shown in Table 1.
[0140] Comparative Example 2 (A-2) modified polyolefin resin 8 mass%, (D-1) polyethylene resin 5 mass%, (E-1) polypropylene resin 5 mass%, (E-2) polypropylene resin 82 mass% were mixed in advance by dry blending, and melt-kneaded using a twin-screw extruder TEX25 (manufactured by JSW Corporation) at a temperature of 200°C, a screw rotation speed of 300 rpm, and an extrusion rate of 20 kg / h. The mixture was extruded into a strand, cooled, and then cut to obtain a pellet-like mixture. Thereafter, a molded product (adhesive sheet) was produced using 100% by mass of the mixture, and each evaluation was performed. The final composition of the easily dismantlable adhesive material and the evaluation results are shown in Table 1.
[0141] [Table 1] [Industrial Applicability]
[0142] The resin composition of the present invention is an adhesive resin composition that has good adhesion between a resin battery case and a metal plate (cooling plate) during use and that allows the metal plate to be easily peeled off from the housing when dismantled, or an adhesive resin composition that has the contradictory properties of good thermal conductivity at all times and excellent insulation during thermal runaway, and therefore has high environmental performance and industrial value. [Explanation of symbols]
[0143] 1 Battery Pack 11 Battery Cells 12 Spacer 13 Metal plate (cooling plate) 14 Adhesive sheet 15 Battery housing 2 Battery pack 21 Battery Cells 22 Spacer 23 Adhesive sheet 24 Metal plate (cooling plate) 25 Battery housing
Claims
1. A resin composition comprising a modified polyolefin resin (A), a thermally expandable flame retardant (Ba), and a copolymer (C) of an α-olefin and an unsaturated carboxylic acid.
2. The resin composition according to claim 1, wherein the thermally expandable flame retardant (Ba) comprises a compound having a melamine structure or a piperazine structure.
3. The resin composition according to claim 1 or 2, wherein the thermally expandable flame retardant (Ba) includes an intumescent flame retardant.
4. A resin composition comprising a modified polyolefin resin (A), a thermally expandable foaming agent (Bb), and a copolymer (C) of an α-olefin and an unsaturated carboxylic acid.
5. The resin composition according to claim 4, wherein the thermally expandable foaming agent (Bb) comprises a chemical foaming agent and / or a physical foaming agent, and a thermoplastic resin capsule that encapsulates the chemical foaming agent and / or the physical foaming agent.
6. The resin composition according to claim 4 or 5, wherein the thermally expandable foaming agent (Bb) comprises a physical foaming agent containing a hydrocarbon compound and a thermoplastic resin capsule that encapsulates the physical foaming agent.
7. 5. The resin composition according to claim 1, wherein the unsaturated carboxylic acid in the copolymer (C) of an α-olefin and an unsaturated carboxylic acid contains maleic anhydride.
8. The resin composition according to claim 1 or 2, wherein the proportion of the thermally expandable flame retardant (Ba) relative to the total mass of the resin composition is 35 mass% or more.
9. The resin composition according to claim 4 or 5, wherein the proportion of the thermally expandable foaming agent (Bb) relative to the total mass of the resin composition is 1 mass% or more.
10. The resin composition according to claim 1 or 4, wherein the modified polyolefin resin (A) is graft-modified with an unsaturated carboxylic acid and / or a derivative thereof.
11. The resin composition according to claim 1 or 4, wherein the modified polyolefin resin (A) has a melting point of 150° C. or lower.
12. The resin composition according to claim 1 or 4, further comprising a polyethylene-based resin (D).
13. The resin composition according to claim 1 or 4, further comprising a polypropylene-based resin (E).
14. A pellet comprising the resin composition according to claim 1 or 4.
15. A molded article obtained by molding the resin composition according to claim 1 or 4.
Citation Information
Patent Citations
Battery modules and battery packs containing them, automobiles
JP2018530896A